Recognition memory span in autopsy-confirmed Dementia with Lewy Bodies and Alzheimer's Disease. (August 2015) - Salmon, David P.; Heindel, William C.; Hamilton, Joanne M.; Vincent Filoteo, J.; Cidambi, Varun; Hansen, Lawrence A.; Masliah, Eliezer; Galasko, Douglas
Abstract: Evidence from patients with amnesia suggests that recognition memory span tasks engage both long-term memory (i.e., secondary memory) processes mediated by the diencephalic-medial temporal lobe memory system and working memory processes mediated by fronto-striatal systems. Thus, the recognition memory span task may be particularly effective for detecting memory deficits in disorders that disrupt both memory systems. The presence of unique pathology in fronto-striatal circuits in Dementia with Lewy Bodies (DLB) compared to AD suggests that performance on the recognition memory span task might be differentially affected in the two disorders even though they have quantitatively similar deficits in secondary memory. In the present study, patients with autopsy-confirmed DLB or AD, and Normal Control (NC) participants, were tested on separate recognition memory span tasks that required them to retain increasing amounts of verbal, spatial, or visual object (i.e., faces) information across trials. Results showed that recognition memory spans for verbal and spatial stimuli, but not face stimuli, were lower in patients with DLB than in those with AD, and more impaired relative to NC performance. This was despite similar deficits in the two patient groups on independent measures of secondary memory such as the total number of words recalled from long-term storage on the Buschke Selective Reminding Test. The disproportionate vulnerability of recognition memory span task performance in DLB compared to AD may be due to greater fronto-striatal involvement in DLB and a corresponding decrement in cooperative interaction between working memory and secondary memory processes. Assessment of recognition memory span may contribute to the ability to distinguish between DLB and AD relatively early in the course of disease. Highlights: Recognition memory span for verbal and spatial stimuli were lower in DLB than AD. DLB had lower spans than AD patients despite similar secondary memory deficits. DLB performed worse than AD patients on standard tests of fronto-striatal function. Poor span performance may be due to additional fronto-striatal dysfunction in DLB. Impaired interaction of working and secondary memory may underlie DLB span deficit.